Which opioid is best for the management of labor pain?. Issue 2 (February 2015) - Okonkwo, Adaobi; Satre, Thomas
Abstract : Evidence‐Based Answer : It is unclear which opioid is the most effective when given by patient‐controlled analgesia (PCA): remifentanil may be more effective than fentanyl (SOR: B, single RCT) and nalbuphine may be more effective than meperidine (SOR: B, single RCT), yet remifentanil is equally effective as meperidine (SOR: A, meta‐analysis). Given as needed intravenously (IV), butorphanol is more effective than either IV fentanyl or IV meperidine (SOR: B, single RCTs).